PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI BERBASIS SPARKOL VIDEOSCRIBE PADA TEMA 7 SUB TEMA 2 SISWA KELAS IV SD NEGERI 030355 PARRATUSAN - Eva Betty Simanjuntak; Astria Hospital Tampubolon (Universitas Negeri Medan, 2021)
This study aims to produce sparkol videoscribe-based animated video learning media, to determine the feasibility of sparkol videoscribe-based animated video learning media and to determine the effectiveness of using Sparkol videoscribe-based animated video learning media on Theme 7 Sub-theme 2 Grade IV Students of SD Negeri 030355 Parratusan. This research and development was carried out using the ADDIE model (Analysis, Design, Development, Implementation and Evaluation) with the research subjects being fourth grade students of SD Negeri 030355 Parratusan. The results of this development research are appropriate and effective learning media to use. The final result by a material expert is 95% or in the “Very Eligible” category. Furthermore, the final result from the media expert is 100% included in the